Haemostatic biomarkers for prognosis and prediction of therapy response in patients with metastatic colorectal cancer. Issue 187 (March 2020) - Moik, Florian; Posch, Florian; Grilz, Ella; Scheithauer, Werner; Pabinger, Ingrid; Prager, Gerald; Ay, Cihan
Abstract: Background: Haemostatic activation and hypercoagulability are frequently observed in patients with metastatic colorectal cancer (mCRC), increase risk of venous thromboembolism (VTE) and have been implicated in tumour proliferation and progression. To date, the association of haemostatic biomarkers with oncologic outcomes including overall survival (OS), progression free survival (PFS) and disease control rate (DCR) is incompletely understood. Methods: Within the framework of the Vienna Cancer and Thrombosis Study, a prospective observational cohort study, we conducted an exploratory analysis to investigate the association of six known biomarkers of haemostasis with oncologic outcomes in 99 patients with mCRC prior to chemotherapy initiation. Results: Patients with high levels of factor VIII activity (FVIII), D-dimer, prothrombin fragment 1 + 2 (F1 + 2) and fibrinogen (defined as levels >75th percentile) had significantly shorter median OS than patients with lower levels. Elevation of four biomarkers was associated with mortality in multivariable analysis, adjusting for age, sex, number of metastatic sites and VTE (hazard ratio [95% CI] for death per doubling of levels: FVIII: 2.06 [1.28–3.30]; sP-selectin: 1.55 [1.07–2.24]; D-dimer: 1.40 [1.18–1.65]; F1 + 2: 1.64 [1.10–2.46]). Patients with elevated levels had numerically shorter median PFS across all markers and disease control rate (DCR) was significantly smaller in those with high levels of FVIII and F1 + 2 (adjusted odds ratio [95% CI] for DCR per doubling of levels: 0.23 [0.09–0.62] and 0.36 [0.16–0.82]) compared to patients with lower levels. Conclusion: Specific elevated haemostatic biomarkers are associated with higher mortality and partially with worse response to chemotherapy in patients with mCRC. Highlights: Haemostatic biomarkers are prognostic in metastatic colorectal cancer. Haemostatic biomarkers are associated with response to chemotherapy in mCRC. Increase of haemostatic biomarkers might reflect more aggressive cancer phenotypes.